2013
DOI: 10.1371/journal.pone.0062122
|View full text |Cite
|
Sign up to set email alerts
|

Applied Mixed Generalized Additive Model to Assess the Effect of Temperature on the Incidence of Bacillary Dysentery and Its Forecast

Abstract: BackgroundAssociation between bacillary dysentery (BD) disease and temperature has been reported in some studies applying Poisson regression model, however the effect estimation might be biased due to the data autocorrelation. Furthermore the temperature effect distributed in the time of different lags has not been studied either. The purpose of this work was to obtaining the association between the BD counts and the climatic factors such as temperature in the form of the weighted averages, concerning the auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 16 publications
6
36
0
Order By: Relevance
“…First, we developed a climate-dysentery model to quantify the relationship between climate factors and dysentery cases. Compared with previously developed models including Tem and Pre (Ma et al 2013), ours incorporated more climate factors to provide a clearer explanation of the relationship between climate change and dysentery incidence. In addition, we validated our developed model using the remaining 25% of data, thereby ensuring the model's reliability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we developed a climate-dysentery model to quantify the relationship between climate factors and dysentery cases. Compared with previously developed models including Tem and Pre (Ma et al 2013), ours incorporated more climate factors to provide a clearer explanation of the relationship between climate change and dysentery incidence. In addition, we validated our developed model using the remaining 25% of data, thereby ensuring the model's reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies merely identified the minimum thresholds for climate factors favorable for dysentery transmission (relative humid-ity>40% and temperature >12.5°C) (Zhang et al 2007), but the maximum values had not been defined. Additionally, only the temperature range (12°C-22°C) suitable for dysentery had been determined (Ma et al 2013), yet the occurrence of dysentery is affected by multiple climate factors. Our study detected the ranges of three climate factors associated with high incidences of dysentery, so it is more valuable for practical prevention and control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is mainly influenced by local poverty levels, living conditions, water storage methods, and personal hygiene habits (Kunii et al, ; Kelly‐Hope et al, ). The incidence of bacillary dysentery in the region has changed significantly, even though the social factors mentioned were stable for an extended period, indicating a connection between the disease and the seasonal variation (Zhang et al, ; Ma et al, ). Meteorological factors have been shown to affect the spread of bacillary dysentery, causing changes in the reproductive rate of Shigella dysenteriae by reducing its incubation period (Patz et al, ).…”
Section: Introductionmentioning
confidence: 99%